Slotline‐based frequency‐reconfigurable quadrature coupler with wide tunable range and simple tuning mechanism. Issue 2 (29th November 2021) - Pan, Yu Fei; Chan, Wing Shing
Abstract: Frequency‐reconfigurable couplers presented before show some shortages such as limited tunable range and complex tuning mechanism. To address these problems, a frequency‐reconfigurable coupler with wide tuning range is proposed based on a slotline structure. A T‐shaped shorted feeding line with certain impedance transform is connected to each port of the coupler. Beneath the shorted end, the slotline structure is utilized to transfer the signal coupled from the feeding line. The 3‐dB quadrature coupler performance is achieved by setting different widths of the slotlines. To tune the frequency, a varactor with tuning capacitance is loaded at the center of each shorted feeding line. Equivalent circuit is given by transmission line model to verify the design concept. For demonstration, the coupler is fabricated and measured. Good agreements between the simulation and measurement and a wide frequency tunable range from 1.2 to 2.6 GHz are achieved based on a single tuning mechanism.